Biogenic carbon in buildings: a critical overview of LCA methods. Issue 1 (12th August 2020) - Hoxha, Endrit; Passer, Alexander; Saade, Marcella Ruschi Mendes; Trigaux, Damien; Shuttleworth, Amie; Pittau, Francesco; Allacker, Karen; Habert, Guillaume
The increasing pressure to reduce greenhouse gas emissions from buildings has motivated specialists to develop low-carbon products incorporating bio-based materials. The impact of these materials is often evaluated through life-cycle assessment (LCA), but there is no clear consensus on how to model the biogenic carbon released or absorbed during their life-cycle. This study investigates and compares existing methods used for biogenic carbon assessment. The most common approaches were identified through an extensive literature review. The possible discrepancies between the results obtained when adopting different methods are made evident through an LCA study of a timber building. Results identified that land-use and land-use-change (LULUC) impacts and carbon-storage credits are not included in most existing methods. In addition, when limiting the system boundary to certain life-cycle stages, methods using the –1/+1 criterion can lead to net negative results for the global warming (GW) score, failing to provide accurate data to inform decision-making. Deviation between the results obtained from different methods was 16% at the building scale and between 35% and 200% at the component scale. Of all the methods studied, the dynamic approach of evaluating biogenic carbon uptake is the most robust and transparent. Practice relevance: This critical review identified key methodological differences between the most commonly used methods and recommended standards for biogenic carbon accounting in buildings. This indicates a lack of consensus and guidance for conducting LCAs of bio-based construction products and buildings using bio-based materials. A case study applying four different LCA approaches on a timber building identified the inability to compare results and create proper benchmarks. Moreover, different methods lead designers to pursue different strategies to reduce a building's carbon footprint. Regulators, the construction industry and the construction products industry are directly affected by this lack of comparability. This research highlights the flaws and benefits of commonly used methods. A clear and grounded recommendation is for practitioners to adopt dynamic biogenic carbon accounting for future assessments of bio-based materials and buildings.